The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1080/10446670410001670436
|View full text |Cite
|
Sign up to set email alerts
|

Testing for Antiphospholipid Antibody (aPL) Specificities in Retrospective “Normal” Cerebral Spinal Fluid (CSF)

Abstract: Antiphospholipid antibodies (aPL) have been found in the blood of patients with systemic and neurological disease. The rare reports of aPL in cerebral spinal fluid (CSF) have been limited mostly to IgG and IgM anticardiolipin (aCL). Our published finding of IgA aPE in the CSF of a young stroke victim prompted us to establish "normal" CSF aPL values for a panel of aPL, which included aCL, antiphosphatidylserine (aPS), antiphosphatidylethanolamine (aPE) and antiphosphatidylcholine (aPC). CSF samples were tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…Previous data 7 have shown that CSF from a normal adult male was observed to be within normal aPL limits, the latter defined by our earlier studies of 59 surgical‐excess CSF samples 18 . After 20 h exposure to hemin, however, we observed a significant redox unmasking in his CSF aPL reactivity, which was greatest for aCL, intermediate for aPS and aPE, and borderline for aPC.…”
Section: Resultssupporting
confidence: 50%
“…Previous data 7 have shown that CSF from a normal adult male was observed to be within normal aPL limits, the latter defined by our earlier studies of 59 surgical‐excess CSF samples 18 . After 20 h exposure to hemin, however, we observed a significant redox unmasking in his CSF aPL reactivity, which was greatest for aCL, intermediate for aPS and aPE, and borderline for aPC.…”
Section: Resultssupporting
confidence: 50%